2013
DOI: 10.2478/s11686-013-0110-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Trypanosoma evansi isolates from water buffaloes (Bubalus bubalis) in the Philippines

Abstract: Trypanosoma evansi infection in the Philippines is frequently reported to affect the country's livestock, particularly, the buffaloes. To assess the prevalence and intraspecific diversity of T. evansi in the country, blood samples from water buffaloes in different geographical regions were collected during an outbreak. T. evansi was detected in all 79 animals tested using PCR targeting the RoTat 1.2 VSG gene. Sequencing of the rDNA complete internal transcribed spacer (ITS) region including the 5.8S subunit sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 57 publications
(46 reference statements)
3
12
0
Order By: Relevance
“…This was supported by study result of Masiga et al (2006) who found a genetic diversity of T. evansi from Kenya according to the amplified fragment length polymorphism/AFLP test (Masiga et al 2006). A genetic variable of T. evansi was also reported based on the expression-siteassociated gene e 6/7 (ESAG6/7) as a marker (Mekata et al 2009;Villareal et al 2013). Trypanosome is able to avoid the immune attack of the host by changing the expression of Variant Surface Glycoprotein (VSG) genes.…”
Section: Introductionsupporting
confidence: 50%
“…This was supported by study result of Masiga et al (2006) who found a genetic diversity of T. evansi from Kenya according to the amplified fragment length polymorphism/AFLP test (Masiga et al 2006). A genetic variable of T. evansi was also reported based on the expression-siteassociated gene e 6/7 (ESAG6/7) as a marker (Mekata et al 2009;Villareal et al 2013). Trypanosome is able to avoid the immune attack of the host by changing the expression of Variant Surface Glycoprotein (VSG) genes.…”
Section: Introductionsupporting
confidence: 50%
“…A partial sequence of RoTat 1.2 VSG gene was identical to the T. evansi sequences reported from India and Kenya, but the varied similarity was seen when aligned with other Egyptian T. evansi sequences [22]. Whilst, analysis of transferrin receptor-encoding gene (ESAG6) showed variable repertoire in the studied isolates, which may indicate to a novel structure of T. evansi population from Egypt and/or a difference in host range [18]. In the present study, the results of the phylogenies obtained from the Maximum Parsimony (MP) method suggest that T. evansi isolates from HSA (Egypt), America and CIV (India) are more diverse than other isolates.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, this study intended to apply TR3/TR4 as a molecular tool to characterize trypanosomes in Egypt. The current search was the third study on T. evansi genotypes in imported dromedary camels in Egypt after [18,22], but it was the first studied T. evansi genotypes in both imported and local camels. A partial sequence of RoTat 1.2 VSG gene was identical to the T. evansi sequences reported from India and Kenya, but the varied similarity was seen when aligned with other Egyptian T. evansi sequences [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations